Dampak Digital Branding dan Kecintaan Merek pada Ekuitas Merek Kosmetik Make Over di Kota Makassar: Peran Mediasi Kepercayaan Merek - Kasim, Nurul Isnaeny; Nofri, Okta; Abdullah, Wahidah (Universitas Islam Negeri Alauddin Makassar, Indonesia, 2023)
ABSTRACT The aims of this study were: 1) To determine the effect of digital branding on brand equity, 2) To determine the effect of brand love on brand equity, 3) To determine the effect of digital branding on brand trust, 4) To determine the effect of brand love on brand trust, 5) To determine the effect of brand trust on brand equity, 6) To determine the effect of brand trust as mediation of digital branding on brand equity, 7) To determine the effect of brand trust as mediation on brand love for brand equity. This research is an associative type of research with a quantitative approach and the research sample is 172 female respondents who use Make Over cosmetics in Makassar City aged 15-29 years. The method for calculating the number of samples uses the Joseph Hair formula and the sampling technique is by means of purposive sampling. This study uses path analysis to analyze data with the help of the SmartPLS program. The results of this study prove that: 1) Digital branding has a positive effect on brand equity, 2) Brand love has a positive effect on brand equity, 3) Digital branding has a positive effect on brand trust, 4) Brand love has a positive effect on brand trust, 5) Brand trust has a positive effect on brand equity, 6) Digital branding has no positive effect on brand equity with brand trust as an intervening variable, 7) Brand love has a positive effect on brand equity with brand trust as an intervening variable. Keywords : Digital Branding, Brand Love, Brand Equity, Brand Trust